The clinical significance of changes in red blood cell distribution width in patients with community-acquired pneumonia - Lee, Sang-Min; Lee, Jae Hyuk; Kim, Kyuseok; Jo, You Hwan; Lee, Jungyoup; Kim, Joonghee; Hwang, Ji Eun; Ko, Young Sang; Ha, Chulmin; Jang, Sujin; Park, Hyunmi (Clinical and experimental emergency medicine, 2016)
Red cell distribution width (RDW) is associated with mortality in patients with community-acquired pneumonia (CAP). However, little is known about the effect of changes in RDW during treatment on mortality. Thus, the objective of this study was to evaluate the association between RDW changes and mortality in hospitalized patients with CAP. Retrospective analyses were performed using medical records of patients hospitalized for CAP from April 2008 to February 2014. The abstracted laboratory values included RDW (from days one to four), clinical variables, and pneumonia severity index (PSI) scores. The ΔRDW was defined as the change in RDW calculated as: (RDW -RDW )/RDW ×100 (%), where 'day n' refers to hospital day. During the study period, a total of 1,069 patients were hospitalized for CAP. The 30-day mortality was 100/1,069 (9.4%). The median RDW at baseline was 14.1% (range, 11.1 to 30.2) and differed significantly between survivors and non-survivors (P<0.05). There were 470 patients with available serial RDW data (30-day mortality 58/470 [12.3%]). Of those, age, PSI score, blood urea nitrogen level, total protein concentration, albumin level, RDW at day 1, and the ΔRDW differed significantly between survivors and non-survivors. Multivariate Cox regression analysis showed that the significance of the relationship between ΔRDW and 30-day mortality risk remained after adjusting for age, PSI score, RDW at day 1, total protein concentration, and initial albumin level. RDW change from day 1 to day 4 was an independent predictor of mortality in patients with CAP.